2013
DOI: 10.5603/cj.a2018.0071
|View full text |Cite
|
Sign up to set email alerts
|

Two-year prognostic value of mean platelet volume in patients with diabetes and stable coronary artery disease undergoing elective percutaneous coronary intervention

Abstract: Background: Mean platelet volume (MPV) is a marker of platelet size and activity, and is associated with a poor prognosis of cardiovascular disease. Studies have shown a relationship between diabetes mellitus (DM) and MPV. This study examined the relationship between admission MPV and 2-year cardiac mortality in patients with DM and stable coronary artery disease (SCAD) undergoing elective percutaneous coronary intervention (PCI). Methods: A total of 1389 patients were enrolled and divided into two groups acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The mean platelet volume is a marker of platelet reactivity and associated with glycaemic level in diabetic patients. Similar to hs‐TnT, the mean platelet volume is also associated with cardiovascular pathologies including atherosclerotic cardiovascular disease, HF and mortality . Our results showed that patients receiving vildagliptin had a significant increase in the mean platelet volume, while those receiving dapagliflozin had a stable mean platelet volume.…”
Section: Discussionsupporting
confidence: 51%
“…The mean platelet volume is a marker of platelet reactivity and associated with glycaemic level in diabetic patients. Similar to hs‐TnT, the mean platelet volume is also associated with cardiovascular pathologies including atherosclerotic cardiovascular disease, HF and mortality . Our results showed that patients receiving vildagliptin had a significant increase in the mean platelet volume, while those receiving dapagliflozin had a stable mean platelet volume.…”
Section: Discussionsupporting
confidence: 51%
“…3). 4,[53][54][55][56] Of these, one was rated good and four were rated fair. Publication year ranged from 2013 to 2019.…”
Section: Mpv In Patients With Stable Cadmentioning
confidence: 99%
“…Five studies presented categorical analyses, comparing high MPV to low MPV. 4,[53][54][55][56] For these studies, the adjusted ORs ranged from 1.10 (95% CI: 0.69-1.77) to 11.36 (95% CI: 2.48-51.99). Two studies reported adjusted HRs of 1.43 (95% CI: 1.10-1.86) and 2.09 (95% CI: 1.08-4.07).…”
Section: Mpv In Patients With Stable Cadmentioning
confidence: 99%
See 2 more Smart Citations